2021
DOI: 10.1021/acscatal.1c00983
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Photoelectron-Transfer Process Characterized by Real-Time Single-Molecule Fluorescence Imaging on Individual Photocatalyst Particles

Abstract: Uncovering the underlying kinetics mechanism of the charge carrier during the transfer process is of fundamental importance in pursuing outstanding photocatalytic activity. However, it still remains a challenge owing to the rapid reaction rate of the charge carrier on the surface of photocatalysts. Here, in situ single-molecule fluorescence microscopy is employed to study the photoelectron-transfer kinetics in real time for an individual TiO2-tipped carbon nanotube (TiO2-tipped CNT) using a redox-responsive fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 48 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Single-molecule localization microscopy can overcome the limitations of ensemble-averaging to identify both inter- and intraparticle heterogeneity in the reactivity of nanostructured catalysts. This super-resolution optical technique uses fluorogenic probes that are chemically activated into their fluorescence state to monitor catalytic turnover events in situ at the single-molecule and single-particle scales. However, a limitation of single-molecule imaging is that the fluorogenic probes used to visualize reaction events do not directly report on the chemical properties that lead to nanoscale variations in activity.…”
mentioning
confidence: 99%
“…Single-molecule localization microscopy can overcome the limitations of ensemble-averaging to identify both inter- and intraparticle heterogeneity in the reactivity of nanostructured catalysts. This super-resolution optical technique uses fluorogenic probes that are chemically activated into their fluorescence state to monitor catalytic turnover events in situ at the single-molecule and single-particle scales. However, a limitation of single-molecule imaging is that the fluorogenic probes used to visualize reaction events do not directly report on the chemical properties that lead to nanoscale variations in activity.…”
mentioning
confidence: 99%
“…The authors determined the photocatalytic activity of single catalysts by monitoring the nanobubble growth kinetics in an operando imaging manner. Very recently, Tang and colleagues explored the photoelectron-transfer kinetics of a typical heterostructure photocatalyst, TiO 2 -tipped CNTs, on an individual particle level by applying a real-time single molecule FLM . This work provides deep insights (theoretical basis) into the photoelectron-transfer processes (kinetics information and behaviors) and guide for designing high performance photocatalysts.…”
Section: Single Particle Detection/imagingmentioning
confidence: 99%
“…This strategy was also used in our previous study, which showed this corrected threshold screening can successfully filter off the background signal. 28 A unique fluorescent blinking pattern was captured (Figure 3A), indicating the signal was collected at a singlemolecule level, which facilitated our localization of every •OH distribution in the subsequent investigation.…”
mentioning
confidence: 92%
“…The produced e – quickly transfers onto the MWCNT, whereas the freshly generated h + on the TiO 2 surface exhibits a strong oxidation potential. In the aqueous phase, a ROS was produced, including the reduction of O 2 with e – and the oxidation of H 2 O with h + . Indeed, •OH is considered the most effective ROS intermediate in the photocatalytic reaction because its oxidation potential is higher than those of other ROS . Therefore, understanding •OH production during the photocatalyst process is crucial for clarifying the photocatalytic mechanism and improving the efficiency of artificial photochemical reactions …”
mentioning
confidence: 99%
See 1 more Smart Citation